Manual adjustment of tube voltage from 120 to 100 kVp during abdominal CT in patients with body weights ≤75 kg: assessment of image quality and radiation dose in a prospective, randomised trial. Issue 6 (June 2016) - Zaehringer, C.; Euler, A.; Karwacki, G.M.; Hohmann, J.; Pansini, M.; Szucs-Farkas, Z.; Schindera, S.T.
Abstract : Aim: To assess image quality and radiation dose in patients with body weights ≤75 kg undergoing abdominal computed tomography (CT) with a tube voltage of either 120 or 100 kVp. Materials and methods: Eighty patients weighing ≤75 kg were prospectively assigned to receive either 120 or 100 kVp abdominal CT in the portal-venous phase. Attenuation values of abdominal organs and image noise were measured, and the contrast-to-noise ratios (CNRs) were calculated. Subjective image quality was assessed by three independent radiologists. Radiation exposure was assessed by size-specific dose estimate (SSDE). Results: The mean attenuation of the kidney increased by 20% at 100 kVp ( p< 0.0001), and the mean image noise was 27% higher in the 100 kVp ( p =0.003). The CNR did not significantly differ between the groups (120 kVp, 6.6±2.8; 100 kVp, 7.4±3.6; p =0.26). Except for subjective image noise ( p< 0.001), no other subjective quality parameters (e.g., contrast, artefacts) were significantly different between the two groups ( p between 0.094 and 0.761). The mean SSDE in the 100-kVp group (9.8±1.8 mGy) was reduced by 19% compared to the 120-kVp group (12.1±1.8 mGy; p< 0.0001). Conclusion: Manual reduction of tube voltage from the standard 120 to 100 kVp for portal-venous phase CT in patients with body weights ≤75 kg resulted in a 19% dose reduction while maintaining objective and subjective image quality. Highlights: Patients weighing ≤75 kg are eligible for 100-kVp abdominal portal-venous CT. 100-kVp abdominal CT reduces radiation dose by 19% compared to 120 kVp. Image quality of 100-kVp abdominal CT is comparable to 120 kVp. 100-kVp abdominal CT for patients weighing ≤75 kg improves patient safety.